Developing Kinesemiotics: Challenges and solutions using the Functional Grammar of Dance - Maiorani, Arianna; Liu, Chun (Frontiers in Communication, 2022)
This article aims to test the applicability and the possibility of adaptation of the Functional Grammar of Dance, which is at the core of the development of the new interdisciplinary research area called Kinesemiotics. As a model of analysis for movement-based communication, the Functional Grammar of Dance has already been used for the analysis of classical ballet choreography, and it is currently employed in a collaborative research project involving the authors of this article and their research group at Loughborough University in the UK, the University of Bremen in Germany, and the English National Ballet. The testing opportunity is provided by the challenging analysis of an iconic choreography of the 20th century: Lamentation, a solo piece created by Martha Graham. The analysis will show the applicability of the theory and the adaptability of the model of analysis, and it will also provide examples of the way a new type of annotation based on this grammar has been created and applied using the ELAN annotation software. The use of ELAN includes the implementation of a specifically compiled controlled vocabulary providing labels for coding the materiality, structure, and semantics of dance discourse systematically.